A Review of The Literature on Islamic Corporate Governance (ICG) In Waqf Entities - Arifin, Jaenal (UIN Sunan Kudus, 2022)
Waqf is a social financial tool that is based on sharia and could help Indonesianefforts to fight poverty.Currently, however, the Waqf literacy index among Indonesians isnot particularlyhigh.The waqf topic has evolved in recent years in terms of research. Thisstudyaimstoanalyzeandevaluatepreviouslyconductedresearchbyidentifyingsimilarities between articles on the same topic. This study focuses on articles onhttps://www.connectedpapers.comthatcontainthekeywords